Ursolic acid from leaf extracts of Barleria lupulina acting as anti clastogenic and anti tumor agent - Das, Pranab Kumar; Sur, Pradip Kumar (Journal of Research in Biology, 2012)
In our previous study, we have reported the radio-protective, anti clastogenic and anti tumor activities of the leaf extract of Barleria lupulina on mice and fish. In the present work, biological active component from the leaf extract has been isolated, by column chromatography. Phytochemical analysis, TLC and NMR studies confirm the presence of ursolic acid as the main anti cancer component, besides other such components, as β sitosterol, sitosterol-3-O-glucoside are also present